Menadione and ethacrynic acid inhibit the hypoxia-inducible factor (HIF) pathway by disrupting HIF-1 alpha interaction with p300 - Na, Yu-Ran; Han, Ki-Cheol; Park, Hyunsung; Yang, Eun Gyeong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
Hypoxia is a general characteristic of most solid malignancies and intimately related to neoplastic diseases and cancer progression. Homeostatic response to hypoxia is primarily mediated by hypoxia inducible factor (HIF)-1 alpha that elicits transcriptional activity through recruitment of the CREB binding protein (CBP)/p300 coactivator. Targeted blockade of HIF-1 alpha binding to CBP/p300 would thus constitute a novel approach for cancer treatment by suppressing tumor angiogenesis and metastasis. Here, we identified inhibitors against the interaction between HIF-1 alpha and p300 by a fluorescence polarization-based assay employing a fluorescently-labeled peptide containing the C-terminal activation domain of HIF-1 alpha. Two small molecule inhibitors, menadione (MD) and ethacrynic acid (EA), were found to decrease expression of luciferase under the control of hypoxia-responsive elements in hypoxic cells as well as to efficiently block the interaction between the full-length HIF-1 alpha and p300. While these compounds did not alter the expression level of HIF-1 alpha, they down-regulated expression of a HIF-1 alpha target vascular endothelial growth factor (VEGF) gene. Considering hypoxia-induced VEGF expression leading to highly aggressive tumor growth, MD and EA may provide new scaffolds for development of tumor therapeutic reagents as well as tools for a better understanding of HIF-1 alpha-mediated hypoxic regulation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: ENDOTHELIAL GROWTH-FACTOR; SIGNAL-TRANSDUCTION; SMALL-MOLECULE; IN-VIVO; ANGIOGENESIS; HYPOXIA-INDUCIBLE-FACTOR-1-ALPHA; CANCER; DOMAIN; CELLS; FACTOR-1-ALPHA